Unique Experiences of Frontline Health Workers involved in management of COVID-19: Stories from Rural Odisha - Choudhary, Hari Ram; Jangir, Hemraj P.; Gupta, Shalu (Advances in Social Sciences Research Journal, 2021)
This narrative study tells the stories of Frontline Health Workers who are actively involved in the management of COVID-19 in the rural areas of Odisha state in India. They have been known as corona warriors by the Government and Media but at the same time, they became the victims of mental and social stigma. Despite their high risk of dealing with corona patients, they worked tirelessly but we as a society started stigmatizing them and failed to give the respect that they deserve. This study is an attempt to highlight their responses to mental and social stigma.